The Role of TIM-3 in Hepatocellular Carcinoma: A Promising Target for Immunotherapy? - Ganjalikhani Hakemi, Mazdak; Jafarinia, Morteza; Azizi, Mahdieh; Rezaeepoor, Mahsa; Isayev, Orkhan; Bazhin, Alexandr V. (Frontiers in Oncology, 2020)
One of the most common tumors in the world is hepatocellular carcinoma (HCC) that its mortality is still on the rise, so it is considered as an important challenge for universal health. Despite the various treatments that have been developed over the past decades, the prognosis of advanced liver cancer is still poor. Recently, tumor immunotherapy has opened new opportunities for suppression of tumor progression, recurrence, and metastasis. Besides, the investigation in this malignancy due to high immune checkpoints expression and the change of immunometabolic programming in immune cells and tumor cells is highly considered. Since anti- cytotoxic T-lymphocyte-associated protein (CTLA)-4 antibodies and anti- programmed cell death protein (PD)-1 antibodies have shown therapeutic effects in various cancers, studies have shown that T cell immunoglobulin mucin-3 (TIM-3), a newly immune checkpoint molecule, play an important role in the development of HCC. In this review, we summarize the recent findings of signal transduction events of TIM-3, its role as a checkpoint target for HCC therapy and immunometabolic situation in progression of HCC.